Pathways to the criminalisation of emotional distress: an offence- and harm-based typology - Peršak, Nina (International journal of law, crime and justice, 2020)
The article examines the criminalisation of causing negative emotional states in others and pursues a principled response to the question under which conditions, in a liberal democratic society, it is legitimate to criminalise human conduct that leads to emotional distress in others. Its main aim is to develop an exploratory typology of different types of legally-relevant emotional distress, based on existing offences and informed by the criteria drawn from criminal law philosophy. Following the conceptual distinction between ‘harm’ and ‘offence’, a typology of legally relevant emotional distress ranging from simpler cases of distress through more in-depth offendedness and offence-plus-harm to states of emotional harm is presented. The article then discusses some ‘hard cases’, such as special vulnerabilities and the question of changing sensibilities through time. The repercussions of these changes for an effective and legitimate criminal justice as well as policy implications are addressed in the concluding section.